Singularity and consciousness: A neuropsychological contribution. Issue 1 (1st February 2021) - de Haan, Edward H. F.; Scholte, Huibert Steven; Pinto, Yair; Foschi, Nicoletta; Polonara, Gabriele; Fabri, Mara
Abstract : In common sense experience based on introspection, consciousness is singular. There is only one 'me' and that is the one that is conscious. This means that 'singularity' is a defining aspect of 'consciousness'. However, the three main theories of consciousness, Integrated Information, Global Workspace and Recurrent Processing theory, are generally not very clear on this issue. These theories have traditionally relied heavily on neuropsychological observations and have interpreted various disorders, such as anosognosia, neglect and split‐brain as impairments in conscious awareness without any reference to 'the singularity'. In this review, we will re‐examine the theoretical implications of these impairments in conscious awareness and propose a new way how to conceptualize consciousness of singularity. We will argue that the subjective feeling of singularity can coexist with several disunified conscious experiences. Singularity awareness may only come into existence due to environmental response constraints. That is, perceptual, language, memory, attentional and motor processes may largely proceed unintegrated in parallel, whereas a sense of unity only arises when organisms need to respond coherently constrained by the affordances of the environment. Next, we examine from this perspective psychiatric disorders and psycho‐active drugs. Finally, we present a first attempt to test this hypothesis with a resting state imaging experiment in a split‐brain patient. The results suggest that there is substantial coherence of activation across the two hemispheres. These data show that a complete lesioning of the corpus callosum does not, in general, alter the resting state networks of the brain. Thus, we propose that we have separate systems in the brain that generate distributed conscious. The sense of singularity, the experience of a 'Me‐ness', emerges in the interaction between the world and response‐planning systems, and this leads to coherent activation in the different functional networks across the cortex.